Implementasi Penilaian Psikomotorik Pembelajaran PAI melalui Unjuk Kerja Tata Cara Sholat di SMP Ma'arif 2 Ponorogo - Zulfa Fauziah (https://ejournal.insuriponorogo.ac.id/, 2024)
This study discusses the implementation of psychomotor assessment in Islamic Religious Education (PAI) learning through the demonstration of prayer procedures at SMP Ma'arif 2 Ponorogo. Psychomotor assessment aims to measure students' practical skills, including movements, readings, and solemnity in prayer. This study uses a descriptive qualitative approach with data collection methods through observation, interviews, and documentation. The results of the study indicate that the demonstration method is effective in improving students' understanding and practical abilities of prayer procedures. Teachers play an important role in providing structured guidance, evaluation, and feedback. When faced with technical constraints such as disruption of learning aids, this affects the smoothness of the process, but can be overcome through teacher adaptation. Psychomotor assessment with the demonstration method not only measures results but also emphasizes the process, thus providing an applicable and in-depth learning experience for students.